2018
DOI: 10.1002/smll.201800190
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Study Reveals Changes in the Molecular Landscape of Human Embryonic Stem Cells with Impaired Stem Cell Differentiation upon Exposure to Titanium Dioxide Nanoparticles

Abstract: The increasing number of nanoparticles (NPs) being used in various industries has led to growing concerns of potential hazards that NP exposure can incur on human health. However, its global effects on humans and the underlying mechanisms are not systemically studied. Human embryonic stem cells (hESCs), with the ability to differentiate to any cell types, provide a unique system to assess cellular, developmental, and functional toxicity in vitro within a single system highly relevant to human physiology. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Some systems are designed to maximize the descriptive output on mechanisms of action of toxicity during cardiomyocyte differentiation, whereas others are designed to prioritize speed, simplicity, and high throughput for screening purposes. The descriptiveness of these assays varies with some focusing on full scale -omics and spatial analysis (Liu et al 2018 ; Pan et al 2018 ; Fu et al 2019 ; Yang et al 2020 ; Lauschke et al 2021a ). Cardiomyocyte contraction is the original apical endpoint from the mEST and is also used in the majority of the publications.…”
Section: Discussionmentioning
confidence: 99%
“…Some systems are designed to maximize the descriptive output on mechanisms of action of toxicity during cardiomyocyte differentiation, whereas others are designed to prioritize speed, simplicity, and high throughput for screening purposes. The descriptiveness of these assays varies with some focusing on full scale -omics and spatial analysis (Liu et al 2018 ; Pan et al 2018 ; Fu et al 2019 ; Yang et al 2020 ; Lauschke et al 2021a ). Cardiomyocyte contraction is the original apical endpoint from the mEST and is also used in the majority of the publications.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased mitochondrial ETC can also limit the contractility of myocardial cells and harm the progeny's heart function and bioenergetics ( 35 , 36 ). Pan et al use of quantitative proteomics approach applying iTRAQ-based mass spectrometry (MS) analysis found that TiO 2 antiparticle may cause human embryonic stem cells (hESCs) to lose their pluripotency and disrupt the differentiation of hESCs mesoderm into cardiomyocytes, thus affecting the normal development of cardiomyocytes, and it was also found that this may be due to DNA damage and oxidative stress in hESCs after TiO2 exposure ( 37 ). Therefore, minimizing titanium exposure during pregnancy is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics study of the TiO 2 NPs effects on the human ESCs revealed the disruption of pluripotency, DNA damage, and apoptotic response (Pan et al 2018). Furthermore, TiO 2 NPs may involved in neurotoxicology by downregulation and upregulation of the Rac1/cdc42 and RhoA proteins respectively, which associate with neural development, axonal outgrowth, neurite formation, and neural differentiation (Hong et al 2018).…”
Section: Titanium Dioxidementioning
confidence: 99%